Validation of Meaning in Life Questionnaire in Hindi (MLQ-H). Issue 5 (27th May 2016) - Singh, Kamlesh; Junnarkar, Mohita; Jaswal, Snehlata; Kaur, Jasleen
ABSTRACT: The primary focus of the study is to present the psychometric properties of the Hindi version of the Meaning in Life Questionnaire (MLQ-H). The study was conducted in North India, where more than one-third of the population speaks Hindi. A total of 826 participants (females = 426) in the age range of 18–60 years volunteered. Consistent with the original factor structure, MLQ-H showed a two-factor structure explaining 56.42% of variance and confirmatory factor analysis established. Both factors demonstrated high internal consistencies with Cronbach's α  = .81 (MLQ-P) and .78 (MLQ-S). Convergent validity was ascertained by correlating with Flourishing Scale (FS) and Scale of Positive and Negative Experience (SPANE). Results demonstrated that MLQ-P positively correlated with SPANE P, SPANE B, and FS, and negatively correlated with SPANE N, whereas the MLQ-S negatively correlated with SPANE B and positively with SPANE N. The results indicate that MLQ-H is a psychometrically sound measure.